HARMONISASI KEKUASAAN LEGISLASI DAN YUDIKATIF DALAM AMANDEMEN LANJUTAN UUD NRI TAHUN 1945 - Tjahyo Rawinarno Tjahyo Rawinarno (NIAGARA Scientific Journal, 2018)
After the amendment to the 1945 Constitution of the Republic of Indonesia, there was a check and balance mechanism legislative mechanisms in Indonesia. The President and DPR RI are state institutions given the power by the constitution to formulate and enact laws. The constitution also gives power to the judiciary to ensure that legislative products are not arbitrary. This condition requires a pattern the relationship in which state institutions given the constitutional mandate understand space the scope of legislative power possessed by each institution.